Effect of drill speed on the strain distribution during drilling of bovine and human bones - Fernandes, M.G.A. (2018)
Drilling is an operation commonly required in orthopaedic surgery for insertion of screws and internal fixation of bone fractures. Induced damage is one of the undesired effects of drilling mainly due to the use of inadequate drilling parameters. During the recent years, scientists have been trying to describe the relationship between drilling parameters and bone injury. However, no studies have examined the level of strain generated in the bone during the drilling process. This paper focuses on the analysis of different drill speeds during drilling of fresh bovine femora and human cadaveric tibiae. The main contribution of this work is to determine how differences in applied drill speeds affect the strain of cortical tissue near the drilling site and the drill bit temperature.